Super gut : a four-week plan to reprogram your microbiome, restore health, and lose weight - Davis, William, 1957- (Hachette Go, 2022)
"Bestselling author of the Wheat Belly franchise brings his next big, game changing idea - the human microbiome and the silent epidemic of SIBO - to the mainstream. There have been other bestselling microbiome books and people think they understand it, but the research is constantly evolving and growing. Dr. Davis has connected the dots between "gut health" and many common, modern ailments and complaints that other books in this category have not, which gives this the potential to be the breakthrough microbiome book. For example, while we are one of the only mainstream publishers with a SIBO book coming out, most are independently published and most doctors are not yet familiar with the term. Dr. Davis is saying that 1 out of 3 people have SIBO, which causes a long list of health issues and illnesses; he sees it as a silent and profound epidemic created by the absence of microbial species that our ancestors had even 50-100 years ago and have been erased by the industrialization of food and medicine. Dr. Davis has also found that patients with dementia have fungi on their brain-SIFO-that has traveled upwards from the intestinal tract! Reprogramming the microbiome based on his research and techniques not only gets to the root of many diseases but also improves levels of oxytocin (the bonding/happy hormone), brain health, and promotes anti-aging and weight loss. He has also found that a small, hand-held device that attaches to your phone can help you measure/diagnose whether or not you have SIBO. All of this is new(s) and the book provides not just the science and case studies but also the recipes and solutions. In this book, he intends to help readers understand the science, diagnose it, eradicate it, and maintain their long term health"--